2005
DOI: 10.1111/j.1365-2958.2005.04735.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of the thioredoxin proteins in Cryptococcus neoformans during stress or virulence and regulation by putative transcriptional modulators

Abstract: SummaryThe thioredoxin system, consisting of thioredoxin, thioredoxin reductase and NADPH, is known to protect cells against oxidative stress. This disulphide reducing system is present in Cryptococcus neoformans and consists of two small, dithiol thioredoxin proteins and one thioredoxin reductase. In this study, we describe the thioredoxin proteins, Trx1 and Trx2, and present their importance not only to stress resistance, but also to the virulence of C. neoformans . Using real-time polymerase chain reaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 36 publications
5
71
0
Order By: Relevance
“…Since 750 M sodium nitrite was toxic to the cryptococcal cells and 500 M appeared to be cytostatic, changes in protein expression were examined with 250 M and 500 M NaNO 2 for 6 h to ensure that the protein changes observed were in response to nitric oxide stress and not due to severe nitric oxide-mediated toxicity. For transcriptional expression changes, a stress of 2 h with 250 M NaNO 2 was used because previous work had shown that changes in the transcriptional profile were apparent at this shorter time point (33,34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 750 M sodium nitrite was toxic to the cryptococcal cells and 500 M appeared to be cytostatic, changes in protein expression were examined with 250 M and 500 M NaNO 2 for 6 h to ensure that the protein changes observed were in response to nitric oxide stress and not due to severe nitric oxide-mediated toxicity. For transcriptional expression changes, a stress of 2 h with 250 M NaNO 2 was used because previous work had shown that changes in the transcriptional profile were apparent at this shorter time point (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic analysis of the nitrosative stress response has not been studied in fungi, though transcriptional responses to RNS have been recently described in S. cerevisiae, C. albicans, and Histoplasma capsulatum (21,39,46). Though the response to nitrosative stress has not been studied in Cryptococcus neoformans, it has been implicated in both stress resistance and virulence of this fungal pathogen (10,33,36). It has been shown that macrophages produce nitric oxide in response to cryptococcal cells (20) and that the anticryptococcal activity of macrophages is mostly dependent on RNS (48).…”
mentioning
confidence: 99%
“…Most of these are limited by their cytotoxic effects on the host, limited efficacy, or development of resistance in the pathogen upon long-term usage (4)(5)(6)(7). In addition, sessile biofilms act as a store house for antibiotic tolerant fungal cells that can lead to persistent systemic infections (8,9). The lack of antifungal agents active against biofilm-forming varieties increases the urgent need for novel agents in the drug pipeline (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance to thermal stress (caused by body temperature) and oxidative stresses (from mammalian host defenses) is critical for successful infection. C. neoformans mutants with increased sensitivity to oxidative or nitrosative challenge, including those lacking superoxide dismutase Sod1 or Sod2 (18,35), alternative oxidase Aox1 (2), flavohemoglobin denitrosylase Fhb1 (23), thiol peroxidase Tsa1 (48), or thioredoxin Trx1 (47), exhibit attenuated virulence. Temperature-sensitive mutants have been isolated in C. neoformans, including cna1 (calcineurin catalytic subunit), cnb1 (calcineurin regulatory subunit), cpa1 (cyclophilin A), and ras1 strains, and all of these have reduced virulence in mammalian host models (3,29,55,73).…”
mentioning
confidence: 99%